UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN SARANA DAN PRSARANA PEMBELAJARAN DI SDN 18 ENGGADANG KECAMATAN PEMANGKAT TAHUN AJARAN 2023-2024 - Habib Habib; Susilawati, Mauizatul Hasanah (ADISAM PUBLISHER, 2024)
This research began with the discovery of the phenomenon of procuring learning facilities and infrastructure which was categorized as adequate despite SDN 18 Enggadang only receiving a small amount of School Operational Assistance Funds (BOS) due to the small number of students. The purpose of this study was to describe and analyze the planning, procurement, and maintenance of the principal in improving learning facilities and infrastructure at SDN 18 Enggadang, Pemangkat District for the 2023-2024 academic year. This research used a qualitative approach with a phenomenological research type. Data collection techniques in this study used interview, observation, and documentation techniques. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The data validity checking techniques used source triangulation, technique triangulation, and member checks. The results of this study indicate that: (1) the principal's planning in improving learning facilities and infrastructure is to map the condition of facilities and infrastructure, then prioritize, then plan the procurement and maintenance budget, (2) the principal's procurement in improving learning facilities and infrastructure is to determine the specifications of the required facilities and infrastructure, then conduct a price survey of goods, then procure according to needs and budget, and (3) the principal's maintenance in improving learning facilities and infrastructure is to divide maintenance tasks, then determine the maintenance budget, then implement a damage reporting system and replacement of learning facilities and infrastructure.